PERITONITIS RESULTING FROM PRIMARY UMBILICAL VEIN CATHETER USE IN NEONATES: A CASE REPORT - Made Melly Mulandari (Universitas Udayana, 2014)
Primary Peritonitis is an infection of the peritoneal cavity which is common inpatients with ascites who are not associated with abdominal disease orretroperitoneal. Cases of primary peritonitis due to umbilical sepsis that occurs fromumbilical catheter as many as 8 cases out of 32 cases of newborns who sufferedperitonitis. This report discusses the case of primary peritonitis in 22 days neonatalwho showed infections which cause used umbilical venous catheter. Imaging finding(BOF) suspected a pneumoperitoneum. Laparotomy surgery on this patient fordiagnostic and drainage ascites fluid. Patient admitted to intensive care (NICU) givenfluid therapy, oxygen, and specific antibiotic (Cefoperasone sulbactam + Amikacinfor 7 days). After 5 days, the patient’s condition improved, so transferred to theneonatal room.